Humillados y ofendidos. Cristianos, judíos y otros contestatarios al culto imperial - Lozano, Fernando (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This article studies the opinion of those opposed to emperor worship.  my goal is to present an alternative approach to these rituals by paying more attention to social elements in conflict with it. I do not seek to deny the wide spread and social success of emperor Worship, but to enrich our understanding of a complex historical phenomenon. The case of senators, pagan writers, christians and roman enemies is assessed. Lastly, it is argued that this official roman State cult turned out to be one of the ways to prove “romanness”. In particular, the crucial defining ritual employed was the sacrifice to the emperor.